Delayed first birth and new mothers' labor market outcomes: Evidence from biological fertility shocks - Massimiliano Bratti; Laura Cavalli (Institute for the Study of Labor (IZA), 2013)
We investigate the impact of delaying the first birth on Italian mothers' labor market outcomes around childbirth. The effect of postponing motherhood is identified using biological fertility shocks, namely the occurrence of miscarriages and stillbirths. Focusing on mothers' behavior around first birth our study is able to isolate the effect of motherhood postponement from that of total fertility. Our estimates suggest that delaying the first birth by one year raises the likelihood of participating in the labor market by 1.2 percentage points and weekly working time by about half an hour, while we do not find any evidence that late motherhood prevents a worsening of new mothers' job conditions (the so-called mommy track). Our findings are robust to a number of sensitivity checks, among which including controls for partners' characteristics and a proxy for maternal health status.
Keywords: J13; J22; 330; delayed first birth; fertility shocks; Italy; labor market; new mothers; Mütter; Weibliche Arbeitskräfte; Fruchtbarkeit; Zeit; Arbeitsangebot; Italien